Management of Critically Ill Patients with Severe Diabetic Ketoacidosis and Acute Renal Failure: A Case Report - Sucipto, Priskila Wulan; I Putu Agus Surya Panji (HM Publisher, 2024)
Background: Diabetic ketoacidosis (DKA) is one of the hyperglycemic crises related to diabetes. The main problem in DKA is ketogenesis, a metabolic process that increases the production and decreases the utilization of ketones. DKA is characterized by a biochemical triad such as hyperglycemia, ketonemia, and high anion gap metabolic acidosis. Management of DKA needs to be carried out appropriately and immediately because it may lead to diabetic coma and death. Case presentation: A 38-year-old woman had decreased consciousness due to metabolic encephalopathy as a complication of severe DKA. The metabolic derangement shows an overlapping high anion gap metabolic acidosis and non-anion gap metabolic acidosis. This case is complicated by acute renal failure. The patient also had been in a hypovolemic state, causing pre-renal acute kidney injury. We treat the patient using a balanced solution to correct hypovolemia. Sonography of the vena cava and blood lactate levels are used to guide fluid resuscitation. We intubate and control the patient's breathing to reduce the metabolic demand. We titrate the insulin infusion until the ketogenesis process is abolished. Antibiotics are given based on sputum culture. Conclusion: Acute renal failure (ARF) is a rare but potentially fatal complication of diabetic ketoacidosis (DKA). Early recognition and aggressive treatment of ARF during DKA may improve the prognosis of these patients.